2015
DOI: 10.1111/adb.12323
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in orexin‐I receptor modulation of motivation for the opioid remifentanil

Abstract: Orexin-1 receptors (Ox1Rs) have been implicated in the motivation for drugs of abuse. Here, we utilized a within-session behavioral-economic threshold procedure to screen for individual differences in economic demand for the ultra-short acting opioid remifentanil and to test whether antagonism of Ox1Rs reduces remifentanil demand. The behavioral-economic procedure revealed robust individual differences in free consumption of remifentanil (Q 0 parameter; hedonic set point). Rats with low baseline Q 0 (low taker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 64 publications
14
75
1
Order By: Relevance
“…FR1 schedule)(44) and high effort paradigms (e.g., PR schedule)(43, 48). Similar to what has been observed in both experimental animals (16, 31, 32, 47) and humans (28, 49), we found that demand elasticity (α) assessed with our within-session BE model accurately predicted meth seeking behaviors in both sexes. Specifically, α (but not Q 0 ) predicted meth seeking on the first day of extinction and during cue-induced reinstatement, which is analogous to what has been shown with cocaine (16).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…FR1 schedule)(44) and high effort paradigms (e.g., PR schedule)(43, 48). Similar to what has been observed in both experimental animals (16, 31, 32, 47) and humans (28, 49), we found that demand elasticity (α) assessed with our within-session BE model accurately predicted meth seeking behaviors in both sexes. Specifically, α (but not Q 0 ) predicted meth seeking on the first day of extinction and during cue-induced reinstatement, which is analogous to what has been shown with cocaine (16).…”
Section: Discussionsupporting
confidence: 86%
“…This newly adapted paradigm for meth allows for assessment of important economic variables within one session, which have previously only been assessed for drugs with a short half-life (i.e., cocaine (25, 34, 35) or remifentanil (47)). In both the multi-day and within-session BE paradigms, we confirmed previous findings that females take more meth than males during both low effort (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are driven by signaling at Ox1R, as pretreatment with the Ox2R antagonist 4PT had no effect on cue-induced cocaine seeking [27]. SB-334867 is also effective at blocking reinstatement of alcohol [34, 35, 46, 47], nicotine [48], and remifentanil [49] seeking, and there is evidence that Ox2R antagonists block reinstatement of nicotine seeking [50], but not cue-induced alcohol seeking [51]. …”
Section: Orexin and Drug Seeking Elicited By External Stimulimentioning
confidence: 99%
“…The OX1R-selective antagonist SB-334867 (SB) decreases seeking of multiple drugs of abuse (Bentzley and Aston-Jones, 2015; James et al, 2012; Mahler et al, 2012; Plaza-Zabala et al, 2012; Porter-Stransky et al, 2015). There is a particularly (though not exclusively) (Anderson et al, 2014; Barson et al, 2015; Brown et al, 2013b; Shoblock et al, 2011) strong relationship between the OX1R vs OX2R and alcohol seeking.…”
Section: Introductionmentioning
confidence: 99%